Surgical Management of Complex Enteric Fistulas in Crohn's Disease - de Campos-Lobato, Luiz Felipe (Clin Colon Rectal Surg, 2019)
Crohn's disease is a chronic, inflammatory bowel condition that can affect the entire digestive tract and in many cases lead to enteric fistula formation. The management of enteric fistulas can be challenging and often requires a multidisciplinary approach.